The Path of Stewardship: Historical Origins and a Reflection on IASB Conceptual Framework Evolution - Gonçalves Barros, Manuela; Tibúrcio Silva, César Augusto (Revista de Contabilidade da UFBA, 2023)
This study aims to present reflections on the historical and cultural origins of accounting stewardship and its evolution as the objective of financial reporting in the IASB’s Conceptual Framework, highlighting the influences of the US and Europe as the result of the most recent Conceptual Framework document. We noted that both the USA and Europe have influenced the current definition of the objective of financial reporting in the IASB’s Conceptual Framework and that the resumption of stewardship in the 2018 document without declaring it as a general objective reinforces the power of influence of the USA and the decision usefulness in the Conceptual Framework convergence process. Although the 2018 Conceptual Framework supports the stewardship culture, its highlight as part of the decision utility contemplates the idea of stewardship developed in the USA, resulting from both the increase of the manager’s power and the need to report on the effectiveness of management in generating return on shareholders. The research contributes to the debate on Conceptual Framework by presenting a critical approach to the evolution of stewardship in this and by discussing the origin of the term from the perspective of contributions from the USA and Europe. Understanding the origin and evolution of accounting stewardship is important since the accounting standards should flow from the stated objectives.